Systematic Literature Review: Batik Tourism as a Strategy to Strengthen Sustainable Business Tourism - Jesica Triane K; Kusumawardhani Annisa Bintang; Uttama Panji Yudha; Ratu Sinar Sari Tanjung; Firda Rahmayanti (Department of Business Administration Politeknik Negeri Sriwijaya, 2026)
Batik is one of Indonesia's cultural heritage that has high aesthetic, social, and economic value. Margacinta and Kondangjajar villages in Cijulang District, Pangandaran Regency, have the potential of Kodja batik that can be developed not only as a cultural attraction but also as a creative economy product that supports sustainable business tourism. This research aims to formulate batik tourism planning that is able to strengthen the sustainable business-based tourism sector. This research method uses the Systematic Literature Review (SLR) approach by examining various relevant previous studies related to the development of batik tourism, sustainable business tourism, and creative economy in local and national contexts. The findings of this literature review are presented further in the Results and Discussion section to identify patterns, opportunities, and challenges in the development of batik tourism as part of sustainable business tourism. The design of a sustainable batik tourism business model is directed at the development of batik tourism clusters that are integrated with Pangandaran natural destinations, so as to provide added value to the local economy, preserve batik culture, and create valuable tourism experiences for visitors.